Recent Studies Toward the Development of Practical Diets for Shrimp and Their Nutritional Requirements - Christian Larbi Ayisi; Xueming Hua; Andrews Apraku; Gyamfua Afriyie; Beatrice Amankwah Kyei (Bogor Agricultural University, Indonesia, 2017)
Shrimp is a very important source of protein which is patronized by almost half of the world's population, and hence a very important specie in aquaculture. There is the need for increase in shrimp production worldwide to meet consumer demands. However, shrimp production is hampered by high cost of commercial feeds. Increase in prices of fish oil and fish meal has led to calls for their substitute. This calls for substitute has resulted in researchers studying the nutritional requirement of shrimp. The rationale for this article is to review the literature available on recent studies toward the development of practical diets for shrimps focusing on the nutrients required by different species qualitatively as well as quantitatively. This review highlights on nutrient requirements with respect to growth and feed utilization. Digestibility of nutrients used in shrimp diets is also accounted for in this article.